Applications of Mathematics Charged Islamic Values by Using Macromedia Flash and Camtasia - Agus Ahmad Durri; Hendri Raharjo; Arif Muchyidin (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2016)
Some factors of low interresting of Mathematic learning material for student on Junior High School grade (SMP/MTs) are design of learning material that is less animation and the difficuties of use the learning material. Therefore, the use of learning material should be inovated for increasing the learners’ interrest, to make them easy understanding the subject that has been learnt, and still capable to increase reigion value in their ownselves. One form of this effort is to create learning material in the form of flash mathematics with consits Islamic value. Flash application is an application that can be developed in accordance animatif developer creativity. The purpose of the research is the developing of learning material in the electric learning form that consists Islamic value in Transformation subject. The method of research is research and development, and the design of the research is using the steps of ADDIE model, there are analysis, design, development, implemetation, and evaluation. Data collection techniques included interviews and observations with research instruments are questionnaires, observation sheets and tests. Further analysis of the data conducted by researchers consists of qualitative and quantitative analysis to determine the feasibility and effectiveness of the teaching materials developed. The results of the expert evaluation consisting of a material expert and a media expert, shows that the average velue obtained from every aspects: content quality and purpose,instructional quality of learning material, aspects of the charge Islamic value, and the technique quality was 4.37 that very good category. The results of the assessment by the teachers of Junior High School grade (MTs) Nurul Huda Munjul which consist of two Mathematics teacher and a teacher of Information and Communication Technology (ICT), shows that the average velue of each aspect was 4.46 with very good category. Than the student quationnaire responses result data obtained by the average velue of each aspects: the quality of learning and instructional, technical aspects of the display, and payload integrition aspects of Islamic value in learning material, namely 3.98, with good categories. The data test scores of student learning outcomes gained an average of 82.34 > KKM (75) with the classical completeness of 89.19% > 85%. The conclusion showed that the quality of Mathematic learning materials charged Islamic velues are developed with macromedia flash and catamsia aplications is feasible and effective to be used in the learning process.